Emotywny odbiór audiodeskrypcji dzieła malarskiego Wassilego Kandinskiego - Jasielska, Aleksandra (Człowiek i Społeczeństwo, 2023)
Psychological models of art reception postulate the presence of two fundamental effects: cognitive understanding and emotional response. Unfortunately, these models are dedicated to sighted viewers. However, even though visually impaired individuals cannot directly perceive artistic creations, audio description enables them to experience the reception of, for example, a painting. In order to answer the question of whether the reception of audio description of a painting triggers similar emotions as the reception of the actual artwork, two independent studies were conducted. The research material was an audio description of Wassily Kandinsky’s abstract watercolour sketch for Composition VII, titled „Untitled”. Subjective experiences were measured using the SUPIN scale. In Study I (N = 138), higher intensity of positive affect was observed compared to negative affect after listening to the audio description. In Study II (N = 67), an increase in positive affect intensity and a decrease in negative affect intensity were observed following the audio description. The results indicate that listening to audio description, which represents an indirect contact with a visual artwork, can improve the well-being of the listeners. The obtained results will be analysed in the context of social construction of emotions and embodied cognition.